Survey dan Inventarisasi Potensi Sumber Daya Air Baku di Wilayah Sungai Progo Opak Serang - Edy Sriyono (Retii, 2020)
The purpose of conducting a survey and inventory of raw water resources in the Progo Opak Serang River Basin is to find out how much potential raw water resources in the river area can be used as raw water for drinking water. Inventory of potential raw water resources is carried out by searching the location, inventorying various potential existing water resources and other relevant information on the location of water resources and the network path to be traversed in order to obtain: information of water resources management planning, secondary data collection and primary data collection. From the potentials of water sources, a score is made to determine the most potential water sources for planning. Scoring is required to determine the location of the selected water source. The survey and inventory results show that the potential of raw water resources that can be utilized in the Progo Opak Serang River Basin as a whole is 68 liters / second. As for the method of taking raw water in general, it can be done with a gravity system, a pump or a combination of both.